Comparison of Intelligence Quotient of Schizophrenic Patients with those of Normal Population (Nepal Medical College Journal, 2019)
An intelligence deficit in schizophrenia is common and is associated with relapse and occupational impairment. The study aims to examine the intelligence quotient of schizophrenic patients and to compare with those of general population. This was a case control study where 30 adult schizophrenic patients between 15 to 45 years were enrolled from the inpatient and outpatient Psychiatry Department of Manipal College of Medical Sciences, Pokhara, Nepal. For control group, 30 normal subjects were enrolled from the general population matched with case group. The intelligence quotients were assessed by Wechsler Adult Intelligence Scale. The prevalence of intelligence deficit was 76.7% in the schizophrenic patients. The mean intelligence quotient was 84.80 with standard deviation of 6.53 in patients with schizophrenia. The intelligence quotient was average or above average in all the general populations. The mean intelligence quotient was 110.63 with standard deviation of 8.74 in the general population. The study concluded that the schizophrenic patients performed poorer in intelligence quotient than the general population